Estudo sobre prospecção dos níveis de conhecimento com ênfase na educação financeira direcionado aos alunos do curso de ciências contábeis - Pacheco, Ítalo Alves (Universidade Federal do Tocantins, 2021)
Financial education is a necessary knowledge, and includes interdisciplinarity related to Social, Economic, Mathematics, Accounting, Law, Administrative and Financial Sciences, among others. Their teaching provides the individual's training to assume the decision-making role, in their economic, personal and collective relations, understanding that education related to finance is an emancipatory practice, which encompasses knowledge and skills for the exercise of citizenship, and should be practiced by the society as a whole, as all establish, at a certain point in their lives, a direct relationship with money. With the increasing complexity of financial products, and the democratization of access to credit, it is essential to train Brazilian families for conscientious consumption. The accounting professional during their graduation receives knowledge about management, budgeting and financial planning, this knowledge is put into practice in serving society that presents itself as entrepreneurs, people, organizations, among others. In this sense, it is necessary to present a basic training of instructions, knowledge, information and experiences, for professional accountant performance, contributing to socioeconomic development, with social responsibility.